A national survey of screening for congenital dislocation of the hip. Issue 5 (May 1996) - Dezateux, C; Godward, S
Abstract : OBJECTIVE: To identify current screening and management practices for congenital dislocation of the hip (CDH), and determine the extent to which ultrasound imaging of the hips is practised throughout the United Kingdom and the Irish Republic. METHODS: Postal questionnaire to paediatricians responsible for the routine neonatal care of infants in all maternity units in the UK and the Irish Republic. RESULTS: Questionnaires were returned for 254 maternity units (92% response rate). By 1994, 69% of maternity units had access to ultrasound imaging of the hips, compared to 14% in 1984. Ultrasound imaging of the hip was not used for universal primary screening, but in 93% of units was undertaken for further assessment of infants with clinically detected hip instability or those identified as being at high risk of CDH, or both. Clinical screening of newborn infants was performed by junior paediatricians, but training with a 'Baby Hippy' hip simulator model was provided in only 37% of units. Treatment of clinically detected hip instability, initiated by an orthopaedic surgeon in 93% of units, varied widely in type and duration. CONCLUSIONS: Ultrasound imaging of the hip is increasingly used in the UK for secondary, rather than primary, screening. Current recommendations are implemented to a variable extent nationally, and the existing wide variation in screening and management for CDH reflects a lack of research evidence to support current screening practices. The effectiveness of screening for CDH needs to be established.